SUSTAINABILITY OF THE SALT EDU-TOURISM AREA IN BUNDER VILLAGE, PADEMAWU DISTRICT, PAMEKASAN REGENCY - Nurul Homisah; Fuad Hasan; Aminah Happy Monintofa Ariyani (GeoEco, 2026)
The salt edu-tourism area in Bunder Village was established to promote local economic development and generate village income by leveraging salt farming as a tourism attraction. However, the initial objectives have not been fully achieved due to declining tourist visits. This study aims to assess the sustainability status of salt edu-tourism across five dimensions—ecological, social, economic, institutional, and infrastructure—and identify leverage attributes to enhance its long-term viability. A quantitative survey approach was employed, involving 30 purposively selected respondents, including tourism managers, residents, and visitors. Data were collected through structured questionnaires and field observations and analysed using the RAPFISH method, incorporating multidimensional scaling and leverage analysis. The results revealed that the overall sustainability of the salt edu-tourism site is categorised as low, with moderate sustainability achieved only in the ecological and institutional dimensions. Key leverage factors include waste management practices, village funding, community engagement, government support, and infrastructure improvements. Compared to previous studies that primarily focused on potential development and socio-economic impacts, this research provides a novel multidimensional sustainability assessment. To improve sustainability, it is recommended to strengthen waste management systems, enhance community participation, secure greater funding, foster strategic collaborations, upgrade infrastructure, and introduce indoor educational facilities. These integrated efforts are crucial to support the future growth and resilience of salt edu-tourism in Bunder Village.